Strategic Management of Health Budget Efficiency in Indonesia's National Health System - Lestari, Yuniati (International Journal Administration, Business & Organization, 2025)
The National Health System (SKN) is a key pillar in achieving equitable public health, but its implementation still faces obstacles in the form of unequal access to services, uneven distribution of health workers, and inefficient financing. This study aims to examine the main challenges in implementing the NHC in Indonesia, formulate relevant strategies to overcome them, and analyze the effectiveness and efficiency of the national health budget within a performance-based policy framework. The study uses a descriptive qualitative approach through a literature review with data sources including government regulations, official reports, and international publications. The results show that SKN is still limited by fragmented governance, low allocation for promotive-preventive efforts, and the dominance of curative spending. However, opportunities for strengthening exist through six pillars of health transformation, including strengthening primary services, improving referral services, system resilience, financing reform, human resource development, and health digitization. The discussion emphasizes the importance of reorienting budget priorities, improving performance accountability, and diversifying funding sources to support the achievement of Universal Health Coverage (UHC) and Sustainable Development Goals (SDGs). This study shows that performance-based budget optimization, governance strengthening, and equitable distribution of resources are key to building a more resilient, inclusive, and sustainable national health system.